2018
DOI: 10.12807/ti.110201.2018.a06
|View full text |Cite
|
Sign up to set email alerts
|

Agency in non-professional manga translation in Iran

Abstract: The present study addresses the phenomenon of online nonprofessional translation of manga in the context of Iran from the perspective of agency. It focuses on the people involved in decision-making in nonprofessional translation production, the non-professional translators' motivations for their free immaterial labor as well as the factors that can constrain or increase their willingness or ability to translate manga into Persian. These questions were answered based on the activities of AnimWorld, the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Globally, we have noted several relevant previous studies that inform this research: motivation and volunteering translation in Russian contexts (Olohan, 2013), motivation in technical translation (Tarasova, Kradetskaya, & Kudlay, 2015), interpreters trainees 'motivation (Wu, 2016), agency and translation (Abdolmaleki, Tavakoli, & Ketabi, 2018), and motivation in translation learning (Liu & Yu, 2019). These studies have covered motivation in translation in different contexts excluding the Indonesian setting.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Globally, we have noted several relevant previous studies that inform this research: motivation and volunteering translation in Russian contexts (Olohan, 2013), motivation in technical translation (Tarasova, Kradetskaya, & Kudlay, 2015), interpreters trainees 'motivation (Wu, 2016), agency and translation (Abdolmaleki, Tavakoli, & Ketabi, 2018), and motivation in translation learning (Liu & Yu, 2019). These studies have covered motivation in translation in different contexts excluding the Indonesian setting.…”
Section: Introductionmentioning
confidence: 93%
“…In Iran, Abdolmaleki et al (2018) explored the online non-professional translation phenomenon. Using the theoretical concept of agency, this study identified that the community of non-professional translator within the Iranian context have a high willingness to translate, despite their ability to translate is limited.…”
Section: Translation and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Manga is popular worldwide, and it has led translation studies to address different aspects of the genre: format (Rota 2008(Rota /2014; scanlation (Rampant 2010); 擬音語 (giongo, words used to mimic sound) and 擬態語 (gitaigo, words used to mimic actions, situations or behaviours that do not involve sound) (Fujimura 2012; Inose 2010); mode fluidity (Huang and Archer 2014); typefaces ( Armour and Takeyama 2015); wine language (Jones and Normand-Marconnet 2016) and agency in non-professional manga translation (Abdolmaleki, Tavakoli and Ketabi 2018;Fabbretti 2019). Nevertheless, manga translations have received less attention than comic translations (Jüngst 2004, 83) because the manga is not accepted as media content, and the researchers have insufficient knowledge of the Japanese language (O'Hagan 2007).…”
Section: Introductionmentioning
confidence: 99%